2023
DOI: 10.3389/fsurg.2023.1102545
|View full text |Cite
|
Sign up to set email alerts
|

Association of clinical outcomes and the predictive value of T lymphocyte subsets within colorectal cancer patients

Abstract: IntroductionTumor immunity is a hot topic in tumor research today, and human immunity is closely related to tumor progression. T lymphocyte is an important component of human immune system, and the changes in their subsets may influence the progression of colorectal cancer (CRC) to some extent. This clinical study systematically describes and analyzes the association of CD4+ and CD8+ T-lymphocyte content and CD4+/CD8+ T-lymphocyte ratio with CRC differentiation, clinical pathological stage, Ki67 expression, T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The immune ability of the patients directly affects the development of tumors, and T lymphocytes play an indispensable role in the fight against tumors. CD4 + T lymphocytes can activate CD8 + T lymphocytes through a variety of pathways to kill tumor cells, and CD3 + -induced lymphocyte proliferation plays a central role in the immune response cascade (McGregor et al, 2004;Yuan et al, 2023). One study showed that Frontiers in Pharmacology frontiersin.org higher levels of CD3 + , CD4 + , and CD8 + were associated with longer survival (Castaneda et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The immune ability of the patients directly affects the development of tumors, and T lymphocytes play an indispensable role in the fight against tumors. CD4 + T lymphocytes can activate CD8 + T lymphocytes through a variety of pathways to kill tumor cells, and CD3 + -induced lymphocyte proliferation plays a central role in the immune response cascade (McGregor et al, 2004;Yuan et al, 2023). One study showed that Frontiers in Pharmacology frontiersin.org higher levels of CD3 + , CD4 + , and CD8 + were associated with longer survival (Castaneda et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation analysis performed in the present study indicated that there is a negative relationship between the levels of CEA and TK1 and the CD3 + T, CD4 + T, and CD8 + T lymphocyte counts. On the other hand, Yuan et al [13] suggested that CD8 + T lymphocytes exhibited a positive correlation with CEA. The differences in conclusions may be attributed to the characteristics of the subjects and the sample sizes involved.…”
Section: Discussionmentioning
confidence: 99%
“…Low and high expression of Ki-67 was defined as positive staining for Ki-67 ≤ 60% and Ki-67 > 60%, respectively. [13,14]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown an association between the densities of CD8+ T lymphocytes in the peripheral blood and the prognosis of various types of cancers, including non-small cell lung, breast, colorectal, pancreatic and bladder cancers [10][11][12][13][14]. In prostate cancer (PCa), most studies have focused on the associations between intratumoral T lymphocyte subpopulations and clinical outcomes [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%